Cash transfers and management advice for agriculture: Evidence from Senegal - Ambler, Kate; de Brauw, Alan; Godlonton, Susan (World Bank, 2020)
This study analyzes impacts of large, one-time cash transfers and farm management plans among farmers in Senegal. Farmers were randomized into groups receiving advisory visits; the visits and an individualized farm management plan; or the visits, the plan, and a cash transfer. After one year, crop production and livestock ownership were higher in the transfer group relative to the group that only received visits. Livestock gains persisted after two years. The evidence suggests the results were driven by increased investment, and, indeed, there is no robust evidence that the management plans alone affected agricultural outcomes.